Extraction of the Proton Charge Radius from Experiments - Kelkar, Neelima Govind; Mart, Terry; Nowakowski, Marek (UI Scholars Hub, 2016)
The static properties of hadrons, such as their radii and other moments of the electric and magnetic distributions, can only be extracted using theoretical methods and cannot be directly measured from experiments. As a result, discrepancies between the extracted values from different precision measurements can exist. The proton charge radius, rp, which is extracted either from electron-proton (e-p) elastic scattering data or from hydrogen atom spectroscopy, seems to be no exception. The value rp = 0.84087(39) fm extracted from muonic hydrogen spectroscopy is about 4% smaller than that obtained from e-p scattering or standard hydrogen spectroscopy. The resolution of this so-called proton radius puzzle has been attempted in many different ways over the past six years. The present article reviews these attempts with a focus on the methods of extracting the radius.